1987
DOI: 10.3109/02844318709083572
|View full text |Cite
|
Sign up to set email alerts
|

General Body Growth In Children With Clefts Of The Lip, Palate, and Craniofacial Structure

Abstract: This paper discusses general body growth in children with craniofacial clefts. Body growth is important in such patients because morphology reflects the cumulation of metabolism over time. The same hormones that direct general body growth also govern the ontogeny of the head and face. Body growth varies in children with different types of clefts. We found no average differences from US norms for those with isolated clefts of the lip alone or those with bilateral clefts of the lip and palate. Children with unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
2
6

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 4 publications
8
52
2
6
Order By: Relevance
“…In one study, 279 patients were studied from birth to the age of 6 years and it was found that the severity of the cleft had no appreciable impact on body weight compared with controls, even though there was an early lag period; by the age of 3 years the children with clefts had caught up with their normal counterparts [7]. A similar outcome was observed in other studies [8,9], but some research has indicated that if a patient has unilateral CLP, or isolated CP, and is male, then there is a possibility of lower body weight [10]. One study used the Swedish Registry of Congenital Malformations (RCM) and the Medical Birth Registry (MBR) to analyse infants with clefts (n 0/2936) and a control group (n 0/2031140) [11], and they found that newborns with CLP (n 0/1139) or CP (n 0/811) weighed relatively less, which is consistent with a later study [12] and were shorter at birth than the control subjects, whereas no differences were found between the group with isolated cleft lip (n 0/865) and the control group.…”
Section: Introductionsupporting
confidence: 63%
“…In one study, 279 patients were studied from birth to the age of 6 years and it was found that the severity of the cleft had no appreciable impact on body weight compared with controls, even though there was an early lag period; by the age of 3 years the children with clefts had caught up with their normal counterparts [7]. A similar outcome was observed in other studies [8,9], but some research has indicated that if a patient has unilateral CLP, or isolated CP, and is male, then there is a possibility of lower body weight [10]. One study used the Swedish Registry of Congenital Malformations (RCM) and the Medical Birth Registry (MBR) to analyse infants with clefts (n 0/2936) and a control group (n 0/2031140) [11], and they found that newborns with CLP (n 0/1139) or CP (n 0/811) weighed relatively less, which is consistent with a later study [12] and were shorter at birth than the control subjects, whereas no differences were found between the group with isolated cleft lip (n 0/865) and the control group.…”
Section: Introductionsupporting
confidence: 63%
“…This study established growth curves for children with UCLP. Many physical growth studies of children with CLP have been published (Bowers et al, 1987;Felix-Schollaart et al, 1992;Ross and Jhonston, 1972; Cunninghan and Jerome, 1997;Becker et al, 1998; Montagnoli et al, 2005, Gopinath andMuda, 2005). Although the results vary between different investigators, most of them state that these children are smaller and lighter than the control subjects, mainly during the first years of age.…”
Section: Setting-hospitalmentioning
confidence: 99%
“…One can therefore assume that a child with cleft lip-palate, without associated genetic syndromes, will follow a growth pattern that is reflected in one of the percentiles of the reference curve; thus, deviations from this growth trajectory should be taken into account in the same way as done for a child without clefts. 4,5 In contrast, other investigators [6][7][8][9] have stated that children with congenital malformations or genetic or clinical syndromes follow their own growth pattern, which might differ from that of normal children, and represent groups with their own disease-specific growth pattern. Thus, deviations from these patterns should always be taken into account when assessing a child with a congenital malformation.…”
Section: Introductionmentioning
confidence: 91%
“…5,[18][19][20] Since these children were in good clinical health at the time of the study, those who did not follow the growth pattern of the group, tending to remain below the cut-off point, should be included in risk groups that need to have their growth monitored more closely. 7 The use of the 10th percentile as the cut-off point for the definition of impaired growth and nutritional status, especially regarding the weight/age ratio, has been criticized 21 because it presents a high proportion of false-positive results compared to the cut-off point defined as -2 z scores proposed by the World Health Organization.…”
Section: Discussionmentioning
confidence: 99%